Detecção de metástases em linfonodos regionais e no sistema nervoso central por imuno-histoquímica em cães com neoplasmas mamários malignos - Barraza, Vanessa Cirinéa Tapia (2024)
This work was divided in two parts, resulting in two scientific articles. In the first article, the aim was to identify metastatic isolated tumor cells (ITCs) in lymph nodes of dogs with tubulopapillary mammary carcinoma, through immunohistochemistry (IHC) for cytokeratin, in which it was not possible to detect neoplastic cells with routine histopathological exam (HE). Additionally, IHC was combined with histochemistry techniques, such as Perls’ Prussian blue and periodic acid-Schiff (PAS), to improve the detection of occult metastases when hemosiderin and/or ceroid were, respectively, present in macrophages of these lymph nodes. The ITCs were found in 24.1% (7/29) of mammary lymph nodes analyzed. These ITCs were located mainly in subcapsular sinuses (4/7; 57.1%). Hemosiderin and ceroid were present in about 90% of the 29 lymph nodes analyzed. In 42.8% (3/7) of lymph nodes with ITCs, hemosiderin and/or ceroid were in the same location of ITCs. It was found that lymph nodes in which ITCs were detected, also present high amounts of hemosiderin (3/7; 42.9%) and low amounts of ceroid (5/7; 71.4%). In this study, IHC combined with histochemistry techniques was a useful method to investigate occult metastases in lymph nodes, mainly when pigments as hemosiderin and ceroid were present. In the second article, the aim was to characterize clinicopathological aspects of dogs with malignant mammary tumors and with neurological involvement, including identification of occult neoplastic cells in the central nervous system (CNS) of these dogs, trough IHC for cytokeratin. There were 26 selected dogs with malignant mammary tumors and with neurological involvement. Based on the results, these dogs were divided in four groups: group 1 (n=7), group 2 (n=11), group 3 (n=4), and group 4 (n=4). The most common histological subtype of primary mammary tumors was tubulopapillary carcinoma (23%). The main neurological signs found were seizures in group 1 and group 2 (4/7; 57,1% and 4/11; 36,4%) and ataxia in group 3 (3/4; 75%). Gross CNS lesions were found mainly as solitary lesions (5/7; 71,4%), and predominantly in occipital cortex (4/7; 57,1% and 2/3; 66,6%) in groups 1 and 4. Histopathological lesions in CNS as malacia, thrombosis, infarct, neovascularization, hemorrhage, and wallerian degeneration were observed in different frequencies in groups 1 to 4. All these lesions were observed in the same neurolocalization of neoplastic cells detected by HE and/or IHC. Neoplastic cells were observed as single tumor cells, micrometastases, and neoplastic emboli. It was located in parenchyma (50-100%), meninges (42,8%-100%), and ventriculi (14,3%-33,3%) in groups 1 to 4. This study allowed the characterization of metastases from mammary tumors to the CNS of dogs. Additionally, through histopathological and IHC analyses it was possible to detected occult metastases, to map their neurolocalization and to observe other simultaneous histopathological lesions in CNS.